ISSUES OF SUSTAINABLE SOCIO-ECONOMIC DEVELOPMENT OF THE REGION IN THE CHANGING ENVIRONMENTAL CONDITIONS OF KARAKALPAKSTAN - M. Q. Niyazimbetov (Modern American Journals, 2025)
The article analyzes the issues of creating a sustainable socio-economic development model in the changing environmental conditions of the Republic of Karakalpakstan. Based on the analysis of sustainable development indicators, regional characteristics and international experiences, the conceptual basis of the adaptive model is described.